Rationale for the choice of strategy positioning for business - Datsyuk, O.; Belova, Tatyana (My University, 2019)
The interpretation of the concept of positioning is considered. It was proved that the idea of market positioning was first introduced by J. Traut. The steps of implementing an effective positioning strategy are substantiated. Necessity of brand positioning is determined. Conditions for choosing a positioning strategy are described.
Keywords: brand positioning; позиціювання бренду; кафедра маркетингу